Houellebecq and the Novel as Site of Epistemic Rebellion - Delphine Grass (Opticon1826, 2006)
Michel Houellebecq is a writer who cultivates an incongruous literary garden, where the necessity of describing contemporary objects as equipment for the manufacture of individuals can be said to precede his concern for literary conventions. This has been at the centre of much criticism formulated around Houellebecq’s novels. One book in particular by Eric Naulleau called Au Secour, Houellebecq Revient! attacks his novels on the grounds that their success relies on his charming the reader by using recognisable elements of everyday life and incorporating them in the novels, in such a way that they could no longer be distinguished from the world of everyday life.
Keywords: epistemology